Organização e funcionamento das salas de recursos multifuncionais em um município paulista - Milanesi, Josiane Beltrame (2012)
In the current national policy for special education from Brazilian Ministry of Educational (MEC) the so-called Multifunctional Resource Classes (SRMs) have been the main locus for the Specialized Educational Services (AEE) offer in the inclusive education perspective. According to official data, from 2005 to 2010, it were available 24,301 SRMs. From this amount 17,679 were for the municipal schools, 6,532 for the state schools, and the others for the federal educational system. This action included 83% of the brazilian cities and it was implemented in 43% of the public schools with enrollment of students belonging to the target audience of the Special Education in the regular system. However, because the complex and dynamic reality involving the educational systems, it is not always that the legal provisions can be implemented in practice. From this, we can ask: how are the systems organizing to comply with the legal provision about the implementation of the SRMs in terms of the operation of these classes, the professionals and the students evaluation? How are the professionals involved implementing and evaluating the SRMs services? This is an important empirical question if one consider that the policy of SRMs implementation is recent and requires the development of researches that can improve the possibilities of pedagogical actions with the students that demand specific interventions, mainly because we adopt the education as public and subjective right. Therefore, the aim of this study is to describe and analyze jointly with educational professionals the SRMs services from a medium-sized city in the São Paulo state, to understand how these professionals are being organized to achieve the legal provisions about the AEE implementation. To answer this question, this is a qualitative and collaborative research, which is, in a first step, a documentary study to feature the policy for special education and, in a second step, based in a cycle of 10 filmed meetings with teachers using the focal groups method; The study was accomplished in the public municipal system of education from the city of Rio Claro in the State of São Paulo covering 23 SRMs teachers and/or teachers of regular classes which had students served by SRMs. Furthermore, management professionals also participate of this study. The contents of the transcribed speeches were analyzed in a jointly work with the participants and resulted in three mainly axes of analysis. The data revealed that the city is trying to attend satisfactorily the current school inclusion policy. Nevertheless, to apply the normative indicated by MEC, many difficulties were encountered. Namely: the organization of the pedagogical work of the SRMs; the requirements for the formation of the specialized teacher and of the regular education; and about the evaluation (for identifying the student, for planning the lecturing and for measuring the learning progress of the student). The results obtained allow for asking if the multifunctional resource classes, as they have worked nowadays, offer adequate support to the schooling of the students with special educational needs in the regular schools.